Semiotics and Verbal Texts : How the News Media Construct a Crisis - Gravells, Jane (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book offers an innovative approach to analysing written texts, grounded in principles of semiotics. Envisaging whole news media representations as 'signs', and using the real-world example of the BP Deepwater Horizon crisis, the author demonstrates how business crises are constructed through language. Gravells identifies patterns of language which show a progression from one kind of 'current news' representation to a different kind of coverage. This coverage positions the crisis as having symbolic and conventional meaning within varied social contexts, including the arts, business and the environment. Using a wealth of examples from the BP story to illustrate her practical research approach, Gravells draws 'language maps' of different phases of the crisis representation, showing how an early 'iconic' phase of representation moves through an 'indexical' to a 'symbolic' phase, and projects a return to a 'naturalised icon'. This book will be of interest to researchers and students of semiotics, those exploring research methods and linguists with an interest in business and media communications.
Keywords: Linguistics.; Communication.; Sociolinguistics.; Discourse analysis.; Semiotics.; elektronické knihy; electronic books